A Case of Cardiac Arrest during C1 Laminectomy for Irreducible Atlantoaxial Subluxation - Yosuke Shibao; Masao Koda; Keita Nakayama; Tomoyuki Asada; Kosuke Sato; Mamoru Kono; Fumihiko Eto; Kentaro Mataki; Hiroshi Kumagai; Katsuya Nagashima; Kousei Miura; Hiroshi Noguchi; et al. (Case Reports in Orthopedics)
We report a case of cardiac arrest, which occurred during C1 laminectomy for irreducible atlantoaxial subluxation, with return of spontaneous circulation (ROSC) upon interruption of the laminectomy. A 60-year-old woman with rheumatoid arthritis presented with neck pain, bilateral finger numbness, and bladder-rectal disturbance. Simple radiograph images showed that the atlantodental interval (ADI) was enlarged to 8 mm, and magnetic resonance imaging revealed severe spinal stenosis at C1. She was diagnosed with cervical spondylotic myelopathy due to atlantoaxial subluxation. Cardiac arrest occurred twice during the C1 laminectomy and occipito-cervical fusion (Occ-C3), and ROSC occurred without any treatment. There was no postoperative worsening of neurological symptoms, and the improvement of sensory and motor palsy was favorable. The pathogenic mechanism was presumed to be trigeminocardiac reflex. Cardiac arrest during upper cervical spine surgery is an important intraoperative complication of which operators should be made aware.